Expose, Oppose, and Confront: The Anti-Racist Movement against the Far-Right Heritage Front in Toronto, 1989 to 1995 - Schwartz, Kristin (PARTECIPAZIONE E CONFLITTO, 2024)
The conflict between anti-racists and the Heritage Front, a far-right organization, in Toronto, Canada, between 1989 and 1995, offers insight into the radical flank effect (RFE) on movement-countermovement dynamics. Through an analysis of media coverage, primary sources, and interviews with past participants, the study shows how Anti-Racist Action (ARA) functioned as a radical flank within the anti-racist movement, contributing to the collapse of the Heritage Front, in part by reorganizing relationships among less militant anti-racists. It reveals how, under certain conditions, radical organizations can remake the political field.